2023
DOI: 10.3390/microorganisms11051143
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Therapy against Escherichia coli and Staphylococcus aureus Using Nanoemulsion-Encapsulated Zinc Phthalocyanine

Abstract: Multidrug-resistant microorganisms have become a significant public health threat, and traditional antibiotics are becoming ineffective. Photodynamic therapy (PDT) is a promising alternative that utilizes photosensitizers and light to produce Reactive Oxygen Species (ROS) that can kill microorganisms. Zinc phthalocyanine (ZnPc) is a promising photosensitizer due to its strong affinity for encapsulation in nanoemulsions and its antimicrobial properties. In this study, nanoemulsion was prepared using Miglyol 812… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…The information provided can help in understanding the binding affinity and other energetics related to the interaction between a Zn(4-PPOx)4Pc as a ligand and its target. This result corroborates the findings that metallophthalocyanines have a strong affinity for proteins from S. aureus, leading to a potent inhibitory effect, while their affinity for proteins from P. aeruginosa and E. coli is comparatively lower, resulting in weaker inhibition [54,55]. Overall, these findings from a molecular docking simulation emphasize that the predicted structural and chemical properties of the S. aureus protein enable it to form more complex and diverse interactions with Zn(4-PPOx) 4 Pc, making it highly susceptible to inhibition.…”
Section: Molecular Electrostatic Potential (Mesp)supporting
confidence: 91%
See 1 more Smart Citation
“…The information provided can help in understanding the binding affinity and other energetics related to the interaction between a Zn(4-PPOx)4Pc as a ligand and its target. This result corroborates the findings that metallophthalocyanines have a strong affinity for proteins from S. aureus, leading to a potent inhibitory effect, while their affinity for proteins from P. aeruginosa and E. coli is comparatively lower, resulting in weaker inhibition [54,55]. Overall, these findings from a molecular docking simulation emphasize that the predicted structural and chemical properties of the S. aureus protein enable it to form more complex and diverse interactions with Zn(4-PPOx) 4 Pc, making it highly susceptible to inhibition.…”
Section: Molecular Electrostatic Potential (Mesp)supporting
confidence: 91%
“…The information provided can help in understanding the binding affinity and other energetics related to the interaction between a Zn(4-PPOx) 4 Pc as a ligand and its target. This result corroborates the findings that metallophthalocyanines have a strong affinity for proteins from S. aureus, leading to a potent inhibitory effect, while their affinity for proteins from P. aeruginosa and E. coli is comparatively lower, resulting in weaker inhibition [54,55].…”
Section: Molecular Electrostatic Potential (Mesp)supporting
confidence: 90%
“…The microwave heating method is superior to conventional heating for synthesizing AgNPs-GSE due to its consistent production of small, uniform nanoparticles with enhanced antibacterial activity and photodynamic inactivation, which inhibits cellular metabolic processes by interacting with photosensitizer molecules. 31 The critical elements in applying photodynamic inactivation are fourfold: visible light, light from the Near-infrared (NIR), reactive oxygen species (ROS), and a photosensitizer that acts as a light sensitizer. 32 The photoinactivation process necessitates a match between the spectrum of visible light used and the absorption spectrum of the photosensitizer.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate prescriptions of ineffective medications in the environment and the regular transmission of microorganisms around the world by travelers also pose serious problems . Many epidemiological investigations have demonstrated that in the last 30 years, bacterial resistance to all known classes of conventional antibiotics has significantly grown, particularly in hospitals, rendering some regimens useless. , According to reports, for instance, methicillin-resistant Staphylococcus aureus type t002 isolates from hospitals in the United States significantly increased in 2013. , According to reports, the centers for disease control and prevention estimated that 10% of patients treated to American hospitals develop a hospital-acquired infection; many of these patients go on to pass away as a result of their diseases . However, the situation is far worse in countries that are developing, where the infection rate is around 75%. To combat the increasing number of resistant bacterial strains that have arisen in this century, however, the most recent developments in the search for new antibiotics fall short .…”
Section: Introductionmentioning
confidence: 99%
“… 30 Many epidemiological investigations have demonstrated that in the last 30 years, bacterial resistance to all known classes of conventional antibiotics has significantly grown, particularly in hospitals, rendering some regimens useless. 31 , 32 According to reports, for instance, methicillin-resistant Staphylococcus aureus type t002 isolates from hospitals in the United States significantly increased in 2013. 33 , 34 According to reports, the centers for disease control and prevention estimated that 10% of patients treated to American hospitals develop a hospital-acquired infection; many of these patients go on to pass away as a result of their diseases.…”
Section: Introductionmentioning
confidence: 99%